Experimental Strategies Presenting a Holistic View Regarding Heat Stress in Plants - Mondal, Sananda; Panda, Debasish; Anyatullah; Bose, Bandana (International Journal of Bio-resource and Stress Management, 2023)
Due to anthropogenic as well as by natural factors the climate of earth is predicted to be warm by an average of 2-4 °C, at the end of the 21st Century. Emission of green house gases (GHG) from agricultural system is one of the major contributing factor in global warming. Heat stress is one of the major abiotic stresses threatening plant growth worldwide. Agricultural crops suffer in presenting their optimum yield potential due to heat stress. Heat stress causes enormous alterations in various processes within the plant system; most of them are well understood from various physiological, biochemical and molecular studies. Heat stress not only affects the morphological and phenological parameters but also the physiological and biochemical parameters like plant water relationship, photosynthesis, assimilate partitioning, hormonal changes, cell membrane stability, production of secondary plant metabolites, antioxidative metabolism, synthesis of heat shock proteins, cell signalling etc. In the advent of climate change and subsequent global warming there is an urgent need for understanding the physiological and biochemical basis of heat stress tolerance in crop plants. There has been a lot of effort worldwide in this regard to develop high temperature tolerant genotypes through transgenic intervention and genetic engineering. This paper reviews the literature supporting evidence for the morphological, phenological, physiological and biochemical effects of heat stress on several plants and different molecular approaches to develop transgenics tolerant to high temperature stress. A plethora of these kinds of plant responses are finally regulated by the genes. Hence, more biotechnological and molecular studies including genomics, proteomics, metaboliomics and the cryptomics are necessary to elucidate the processes further.